Frequency and Molecular Identification of Cryptosporidium in Adult Prim’Holstein Dairy Cattle Farms in the North of France - Gabriela Certad; Nausicaa Gantois; Sophie Merlin; Sophie Martel; Gaël Even; Eric Viscogliosi; Christophe Audebert; Magali Chabé (Microorganisms, 2024)
Cryptosporidium apicomplexan protozoa are ubiquitous intracellular agents affecting humans and animals. In particular, bovine cryptosporidiosis is recognized as endemic worldwide. However, epidemiological investigations remain limited in France regarding the burden of these parasites in cattle. To improve our understanding of the epidemiology of cryptosporidiosis, the main aim of this study was to determine the frequency and the genetic diversity of Cryptosporidium in adult Prim’Holstein dairy cattle farms in the north of France. Fecal specimens were collected from 1454 non-diarrheic and non-pregnant animals (nulli-, primi-, or multiparous) throughout 20 farms in an area of 110 km around Lille. For Cryptosporidium species identification, nested PCR followed by sequence and phylogenetic analyses were used. The overall frequency of Cryptosporidium spp. in-fection was 30.00% (C.I. 95%: 12.83–54.33) in farms and 0.89% (C.I. 95%: 0.498–1.57) at the individual level. In primi- or multiparous cows, only C. andersoni was found. C. ryanae, C. bovis/xiaoi and C. andersoni were detected in heifers. The phylogenetic tree confirmed that analyzed sequences were grouped with known reference sequences reported in dairy cattle. Further studies on the cumulative prevalence, risks factors and pathogenicity are needed to give a more accurate assessment of the impact of Cryptosporidium infection in dairy cattle in France.